Buletin Peternakan : Pertumbuhan Kompensasi Ayam Betina Hasil Persilangan Antara Ayam Kampung Jantan Dengan Ayam Ras Petelur Betina Yang Mendapat Level Protein Pakan Masa Starter Berbeda - Harimurti Februari Trisiwi (Peternakan UGM, 2016)
The experiment was conducted to examine the effect of various dietary protein levels during starting period (0-9 weeks) on compensatory growth period (9-12 weeks) of crossbred hens between cockerel native chicken and laying hens. Thirty two day old chicks were randomly divided into four different groups.